2021
DOI: 10.3390/ijerph18105427
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Experiences of Facilitators for and Barriers to Maintaining Exercise 12 Months after a Group-Based Intervention for Depression

Abstract: Exercise can improve health among adolescents with depression. Understanding facilitators for and barriers to maintaining exercise among adolescents with depression may increase adherence to exercise and consequently improve health. The aim was to explore adolescents’ experiences of facilitators for and barriers to maintaining exercise after a group-based exercise intervention for depression. Interviews (n = 14) were conducted 12 months after the exercise intervention. A qualitative content analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
(64 reference statements)
1
20
1
Order By: Relevance
“…Seven articles ( Douthitt, 1994 ; Bruner and Spink, 2011 ; Birt et al, 2014 ; Alberga et al, 2019 ; Guerrero et al, 2020 ; Faulkner and Michaliszyn, 2021 ; Sunesson et al, 2021 ) were kept for review and related information is shown in Table 1 . The results summarized below were presented according to the purposes of the current review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles ( Douthitt, 1994 ; Bruner and Spink, 2011 ; Birt et al, 2014 ; Alberga et al, 2019 ; Guerrero et al, 2020 ; Faulkner and Michaliszyn, 2021 ; Sunesson et al, 2021 ) were kept for review and related information is shown in Table 1 . The results summarized below were presented according to the purposes of the current review.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Faulkner’s study explored the children and adolescents with obesity and type 2 diabetes ( Faulkner and Michaliszyn, 2021 ). The qualitative studies all used semi structured interviews, with 19 healthy children and adolescents in Birt’s study and 14 children and adolescents with depression in Sunesson’s study ( Birt et al, 2014 ; Sunesson et al, 2021 ). Of the seven studies included, only one examined both individual and social positive psychological factors influencing children and adolescents’ exercise adherence ( Sunesson et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manageability of the intervention was based on a supportive environment, where supportive and encouraging adults and the feeling of belonging to a peer group were important. Support from those around the teenagers, such as family, healthcare professionals, coaches, and fellow group members, was important and facilitated adherence and commitment to the exercise intervention [ 18 , 19 ]. In the present study, extensive support from health professionals, with reminders, phone calls, pep talks, and personal participation in sessions, together with family support, was of utmost importance for compliance, albeit it might be challenging to implement in usual care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…After completing an exercise intervention aimed at lowering depressive symptoms, many adolescents describe positive changes in their attitudes to exercise and in relation to their exercise habits [8,18]. Qualitative studies describing long-term evaluations of health behaviour after an exercise intervention for adolescent depression are scarce, but Sunesson et al (2021) identified improved self-esteem and a supportive environment as facilitators in the maintenance of exercise one year after participating in the intervention, while disease burden and a lack of a supportive environment were identified as barriers [19].…”
Section: Introductionmentioning
confidence: 99%